Aprostocetus nitens (Hymenoptera: Eulophidae), an Ectoparasitoid Proposed for Biological Control of the Destructive Erythrina Gall Wasp, Quadrastichus erythrinae, in Hawaiʻi - Mohsen M. Ramadan; Juliana A. Yalemar; Daniel Rubinoff; Mark G. Wright; Aimé H. Bokonon-Ganta; Xingeng Wang (Insects)
Aprostocetus nitens Prinsloo & Kelly (Hymenoptera: Eulophidae) was identified as one of four hymenopteran ectoparasitoids utilizing three erythrina gall wasps, Quadrastichus bardus, Q. erythrinae, and Q. gallicola) (Hymenoptera: Eulophidae) in the native eastern Africa. In Hawaiʻi, the eurytomid wasp, Eurytoma erythrinae Gates & Delvare (Hymenoptera: Eurytomidae), was introduced and approved for statewide release in 2008 to control the erythrina gall wasp (EGW) Q. erythrinae Kim. EGW has devastated the wiliwili trees, Erythrina sandwicensis Degener (Fabaceae), an ecologically and culturally important native Hawaiian tree species. However, the parasitoid’s impact on the galled inflorescences and shoots was not adequate to ensure adequate seed set and maturation for successful tree recruitment. Aprostocetus nitens was thus evaluated as a prospective natural enemy to enhance the biological control of EGW to further protect the wiliwili trees in Hawaiʻi. Both choice and no-choice host specificity tests were conducted on seven non-target gall formers in the Hawaii Department of Agriculture, Insect Containment Facility, and showed that the parasitoid was extremely specific to EGW. The potential for competition between this parasitoid and the established E. erythrinae was also investigated, showing that the release of a second parasitoid will potentially complement the success of the eurytomid wasp for control of EGW. Unlike what was found in the native region, the Hawaiian laboratory colony is thelytokous, producing only female offspring. The life cycle took 20.1 ± 0.28 days under the laboratory conditions. Non-ovipositing female survived for 102.5 ± 2.9 days when fed honey and laid eggs for 25.1 ± 2.3 days with average fecundity of 156.7 ± 22.3 offspring/female. This value is 3.9-fold higher than offspring produced by E. erythrinae. Aprostocetus nitens, host specificity, competition with E. erythrinae, and its tri-trophic association with 15 Erythrina host plants and 5 gall wasp assemblages in the native African regions were defined. Implications to reduce frequent galls on the native Erythrina plants and likely domination over E. erythrinae, are discussed.